Performance studies on cryogenic treated carbide cutting tool for turning of AISI304 steel - Patil, Nagraj; K., Gopalakrishna; B., Sangmesh; Sudhakar, K.; Vijayakumar, G. C. (Penerbit Universiti Malaysia Pahang, 2018)
This paper attempts to compare and contrast cryogenic treated and untreated carbide cutting tool in turning operation of AISI304 steel. Machining parameters, namely cutting speed, feed rate and depth of cut are optimized for cryogenic treated tools. Tool life of the insert was determined based on the tests performed such as hardness, surface roughness and maximum wear. A design of experiments (DOE) and an analysis of variance (ANOVA) have been incorporated in the study. The objective of the paper is to determine the effects of each parameter on the surface roughness and tool wear. Material characterization was carried out using scanning electron microscope (SEM) and the maximum wear was estimated using optical microscope before and after the cryogenic treatment. The experimental results showed that cryogenic treated cutting tools significantly reduction in surface roughness, improves resistance to wear than untreated one. A confirmation test was performed between experimental and optimum values and the results are found to be in good agreement.